Enhanced learning: Designing bifocal modeling practicum tools with ESP32 for exploring kinetic theory of gases - Sujito Sujito; Sulur Sulur; Muhammad Nur Hudha; Nanang Winarno; Sunardi Sunardi (Momentum: Physics Education Journal, 2024)
This research was conducted to obtain an initial design for a laboratory practical tool based on bifocal modeling assisted by an ESP32 microcontroller for kinetic gas theory. This study was conducted to obtain an initial design for a practical laboratory tool based on bifocal modeling assisted by the ESP32 microcontroller on the kinetic theory of gases. This study was conducted descriptively through a literature review of various book articles and materials. Interviews were conducted with students and physics teachers in high schools (9 students and two teachers in Malang, 15 students and three teachers in Bandung) in Indonesia. Interviews were conducted to obtain an overview of the application of physics learning and reveal other potential problems students and teachers face. The design of the bifocal modeling tool developed has been consulted with physics and ICT learning experts. The results are that it needs to be further developed and maintained until the manufacturing stage. Bifocal modeling based on the design developed in this study has the potential to facilitate students to conduct scientific experiments related to the kinetic theory of gases. Based on the equipment to be developed, it is expected that students will be able to observe macroscopic gas phenomena through actual experiments, monitor microscopic phenomena visualized through computer models, collect data in actual experiments and computer simulations, and compare data. Students' understanding of the concept of the kinetic theory of gases has the potential to be improved by conducting practical work using bifocal modeling-based tools.